Dasar-dasar Pendidikan Islam Perspektif Hasan Langgulung dan Relevansinya di Era Disrupsi: The Fundamentals of Islamic Education from Hasan Langgulung's Perspective and Its Relevance in the Era of Disruption - Samsuddin, Samsuddin; Abdul Jabar Idharudin; Agusman, Agusman (Litera Academica Publishing, 2025)
This study aims to explore the relevance of the fundamental principles of Islamic education according to Hasan Langgulung to the needs of modern education, as well as the implications of their application in facing global challenges in the era of disruption. The method used is a qualitative approach with descriptive analysis, through literature review and interpretation of the fundamental concepts of Islamic education proposed by Hasan Langgulung. The research findings indicate that the fundamental principles of Islamic education, including wholeness (syumuliyah), integration, authenticity, scientific, practical, solidarity, and openness, are highly relevant to contemporary education. Each principle supports the creation of holistic education, which develops not only intellectual aspects but also spiritual, moral, and social dimensions. The results emphasize that with a systematic and adaptive approach, Hasan Langgulung's concept of Islamic education can be a solution to produce generations who are not only excel in knowledge but also possess high integrity in facing global dynamics. The implications of these findings highlight the importance of integrating both worldly and otherworldly knowledge in the education curriculum, as well as strengthening social and moral values within the education system. As a recommendation, educators and policymakers are encouraged to implement these fundamental principles in designing curricula that are more relevant to future challenges.